Optical laminate and image display device having the same
By stacking laminates with specific structures on ultra-thin glass and controlling the elastic modulus of the base resin layer, the problems of insufficient pencil hardness, poor bending resistance and curling in ultra-thin glass during use are solved, and the excellent performance and processability of the optical laminate are achieved.
Patent Information
- Application Number
- CN202410930602.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-02-29
- Filing Date
- 2024-07-11
- Publication Date
- 2025-03-07
AI Technical Summary
When used, existing ultra-thin glass has problems such as insufficient pencil hardness, poor bending resistance and possible curling, which affects its processability.
The structure is adopted to stack the primer layer, the base resin layer and the functional coating in turn on ultra-thin glass, and the pencil hardness, bending resistance and curling characteristics of the optical laminate are ensured by controlling the elastic modulus of the base resin layer and the total thickness ratio of the laminated body.
The excellent pencil hardness characteristics of the optical laminated body are realized, ensuring its bending resistance, while avoiding curling and improving processability.
Smart Images

Figure CN119575519A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an optical laminate and an image display device having the optical laminate, and more specifically to an optical laminate of a glass substrate and an image display device having the optical laminate. The optical laminate not only has excellent pencil hardness characteristics and can ensure bending resistance, but also does not produce curling, and thus has excellent processability. Background Art
[0002] With the recent development of display technology, foldable displays, rollable displays, stretchable displays, etc. have been developed. Therefore, in order to protect these different types of displays, ultra-thin glass (UTG) with improved flexible characteristics has been actively developed.
[0003] This ultra-thin glass has flexible properties, so excellent bending strength is required for use in various types of displays. In addition, in order to improve the quality of the display, the surface roughness needs to be increased.
[0004] Generally, in order to reduce the possibility of scratches on the glass surface of the window glass during use of the display and the possibility of damage due to falling during use, ion exchange chemical strengthening is used to improve the strength of the window glass used in mobile displays.
[0005] For example, Korean Patent Publication No. 10-1999-0042313 discloses a method of strengthening glass for a display.
[0006] However, despite the chemical strengthening treatment, ultra-thin glass is still too thin, so when using it, it is necessary to attach a protective film with a soft adhesive to prevent flying, etc. However, this weakens the hardness of the pencil, so there are problems such as leaving marks when using the pen.
[0007] Alternatively, when a coating layer of a resin material is formed on an ultra-thin glass to prevent scattering or to increase surface hardness, curling may occur due to shrinkage stress caused by curing of the coating layer, thereby causing a problem of deteriorating processability. Summary of the invention
[0008] Technical issues
[0009] An object of the present invention is to provide an optical laminate of a glass substrate which has excellent pencil hardness characteristics and can ensure bending resistance, and also does not cause curling, thereby having excellent processability.
[0010] Another object of the present invention is to provide an image display device having the optical laminate.
[0011] Technical Solution
[0012] In one aspect, the present invention provides an optical stack, comprising:
[0013] Glass substrate;
[0014] A primer layer formed on one surface of the glass substrate;
[0015] a base resin layer formed on the primer layer; and
[0016] a functional coating layer formed on the substrate resin layer,
[0017] The glass substrate is an ultra-thin glass with a thickness of less than 100 μm.
[0018] The elastic modulus of the substrate resin layer is 3.3 GPa to 5.2 GPa,
[0019] The pencil hardness of the optical laminate as a whole is 2H or more, and
[0020] The optical stack satisfies the following mathematical formula 1:
[0021] [Mathematical formula 1]
[0022] 0.1≤d2 / d1≤0.4
[0023] In the mathematical formula 1, d1 is the thickness of the glass substrate, and d2 is the total thickness of the primer layer, the substrate resin layer, and the functional coating layer.
[0024] The optical laminate according to one embodiment of the present invention may have a total thickness of less than 120 μm.
[0025] In one embodiment of the present invention, the primer layer may be formed of a primer layer-forming composition including at least one of a polyurethane resin and a polyester resin.
[0026] In one embodiment of the present invention, the primer layer may be formed of a primer layer-forming composition including a water-dispersible polyurethane resin and a stabilizer, wherein the stabilizer may include a primary thermal stabilizer and an auxiliary thermal stabilizer.
[0027] In one embodiment of the present invention, the primary heat stabilizer may be at least one selected from phenolic heat stabilizers and amine heat stabilizers, and the auxiliary heat stabilizer may be at least one selected from phosphorus heat stabilizers and sulfur heat stabilizers.
[0028] In one embodiment of the present invention, the base resin layer may be formed of a base resin layer-forming composition containing at least one resin of a polyimide resin and a polyamide-imide resin.
[0029] In one embodiment of the present invention, the functional coating may be a hard coating.
[0030] In one embodiment of the present invention, the hard coating layer may be formed of a hard coating composition including a light-transmitting resin, a fluorine-based UV-curable functional group-containing compound, a photoinitiator, and a solvent.
[0031] In another aspect, the present invention provides an image display device including the optical laminate.
[0032] In yet another aspect, the present invention provides a window of a flexible display device having the optical laminate.
[0033] In another aspect, the present invention provides a polarizing plate having the optical laminate.
[0034] In yet another aspect, the present invention provides a touch sensor having the optical stack.
[0035] In still another aspect, the present invention provides a variable transmittance optical stack including the optical stack.
[0036] In yet another aspect, the present invention provides a smart window including the variable transmittance optical stack.
[0037] Effects of the Invention
[0038] The optical laminate according to the present invention has a structure in which a primer layer, a substrate resin layer and a functional coating layer are sequentially stacked on an ultra-thin glass so that the ratio of the total thickness of the primer layer, the substrate resin layer and the functional coating layer to the thickness of the glass substrate is controlled within a specific range, and the elastic modulus of the substrate resin layer is controlled within a specific range, so that it not only has excellent pencil hardness characteristics and can ensure bending resistance, but also does not generate curling, and thus has excellent processability. Specifically, the optical laminate according to one embodiment of the present invention exhibits a pencil hardness of 2H or more, so that no marks are left when a pen is used. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 is a schematic cross-sectional view of an optical layered body according to one embodiment of the present invention. DETAILED DESCRIPTION
[0040] Hereinafter, the present invention will be described in more detail.
[0041] One embodiment of the present invention relates to an optical layered body, comprising:
[0042] Glass substrate;
[0043] A primer layer formed on one surface of the glass substrate;
[0044] a base resin layer formed on the primer layer; and
[0045] a functional coating layer formed on the substrate resin layer,
[0046] The glass substrate is an ultra-thin glass with a thickness of less than 100 μm.
[0047] The elastic modulus of the substrate resin layer is 3.3 GPa to 5.2 GPa,
[0048] The pencil hardness of the optical laminate as a whole is 2H or more, and
[0049] The optical stack satisfies the following mathematical formula 1:
[0050] [Mathematical formula 1]
[0051] 0.1≤d2 / d1≤0.4
[0052] In the mathematical formula 1, d1 is the thickness of the glass substrate, and d2 is the total thickness of the primer layer, the substrate resin layer, and the functional coating layer.
[0053] The d2 / d1 value of the optical layered body according to one embodiment of the present invention is 0.1 to 0.4, preferably 0.1 or more and less than 0.3.
[0054] In the present invention, d1 is the thickness of the glass substrate, and d2 is the total thickness of the primer layer, the substrate resin layer, and the functional coating layer.
[0055] If the d2 / d1 value is less than 0.1, the hardness property may be low enough to cause cracking of the underlying glass substrate when measuring the pencil hardness property, and if the d2 / d1 value is greater than 0.4, the curling property may be poor.
[0056] In the optical layered body according to one embodiment of the present invention, the elastic modulus of the base resin layer is controlled to be 3.3 GPa to 5.2 GPa.
[0057] By controlling the elastic modulus of the base resin layer to 3.3 to 5.2 GPa, preferably 3.8 to 5.2 GPa, more preferably 4.6 to 5.2 GPa, the bending resistance, pencil hardness, and curling characteristics of the optical laminate can be simultaneously ensured.
[0058] If the elastic modulus of the substrate resin layer exceeds 5.2 GPa, the shrinkage stress proportional to the product of curl (strain) and the elastic modulus caused by the shrinkage during drying of the substrate resin layer is large, and even after the bonding operation of the display module, the shrinkage stress affects the entire module, which may cause the curling tendency of the bending functional coating to increase, and if it is less than 3.3 GPa, the elastic modulus of the substrate resin layer itself is insufficient, resulting in reduced resistance and recovery to deformation caused by external forces, which may cause the pencil hardness of the substrate resin layer itself to decrease, and ultimately reduce the pencil hardness of the optical laminate as a whole.
[0059] The elastic modulus is a numerical value that indicates the rigidity of a material and is also called the coefficient of elasticity. The elastic modulus is defined as the ratio of stress to strain in the elastic region and can be determined from the slope of the linear elastic region in the stress-strain curve obtained by performing a tensile test on a specimen of the material.
[0060] Specifically, the elastic modulus of the substrate resin layer can be measured in a stretching evaluation mode using a universal testing machine (UTM). The substrate resin layer can be deposited on a glass not formed with a primer layer, dried, and then peeled off to obtain only the substrate resin layer. The substrate resin layer obtained in this way can be made into a test piece for stretching evaluation using a super cutting mechanism according to the JIS-K7139 rod type standard, and measured with a pulling speed of 4mm / minute under the stretching evaluation mode of the universal testing machine.
[0061] The elastic modulus of the base resin layer can be adjusted by controlling the type and molar ratio of the repeating units constituting the resin, the weight average molecular weight of the resin, and the like.
[0062] The pencil hardness of the entire optical layered body according to one embodiment of the present invention is 2H or more, preferably 4H or more.
[0063] The pencil hardness can be measured as follows: the optical laminate is fixed so that the functional coating is located on the top, and then the measurement operation of the pencil hardness test is repeated 5 times with a load of 750 gf on the surface of the functional coating at a length of 1 cm. During the measurement, if an abnormal appearance such as scratches appearing 4 or more times is not found, the hardness of the pencil used in the test is taken as the pencil hardness. For example, if the test operation is performed 5 times with a 2H pencil and no abnormal appearance appears 4 or more times, the pencil hardness of the material is 2H or more.
[0064] If the pencil hardness of the entire optical laminate is less than 2H, an indentation may be left when a pen is used, or recovery from the indentation may take a long time.
[0065] The optical layered body according to one embodiment of the present invention may have a total thickness of less than 120 μm, for example, 35 μm or more and less than 120 μm. If the total thickness of the optical layered body is 120 μm or more, it may be difficult to ensure bending resistance.
[0066] The optical laminate according to the present invention has a structure in which a primer layer, a substrate resin layer and a functional coating are stacked sequentially on an ultra-thin glass so that the ratio of the total thickness of the primer layer, the substrate resin layer and the functional coating to the thickness of the glass substrate is controlled within a specific range and the elastic modulus of the substrate resin layer is controlled within a specific range. It not only has excellent pencil hardness characteristics and can ensure bending resistance, but also does not produce curling, so it has excellent processability. Specifically, the optical laminate according to one embodiment of the present invention exhibits a pencil hardness of more than 2H, so it does not leave marks when using a pen. In addition, the optical laminate according to one embodiment of the present invention can ensure flexibility even at a radius of curvature of 3mm. In addition, the optical laminate according to one embodiment of the present invention exhibits antifouling, wear resistance and chemical resistance.
[0067] Figure 1 This is a cross-sectional view of the structure of an optical layered body according to one embodiment of the present invention.
[0068] Reference Figure 1 , an optical laminate 100 according to an embodiment of the present invention includes a glass substrate 110 , a primer layer 120 , a substrate resin layer 130 , and a functional coating layer 140 which are sequentially laminated.
[0069] Hereinafter, each member of the optical stack will be described in detail.
[0070] The glass substrate 110 is ultra-thin glass (UTG) having a thickness of less than 100 μm. For example, the thickness of the glass substrate 110 is greater than 10 μm and less than 100 μm, preferably 20 μm to 95 μm, and more preferably 30 μm to 90 μm.
[0071] If the thickness of the glass substrate is 100 μm or more, the bending resistance may be low.
[0072] The ultra-thin glass may include one or more selected from the group consisting of aluminoborosilicate, borosilicate, alkali metal lead silicate, soda lime, lithium aluminosilicate and aluminosilicate, and preferably may include one or more selected from the group consisting of soda lime, lithium aluminosilicate and aluminosilicate.
[0073] The ultra-thin glass may be cut into units by cutting the original sheet, and the cut surface, i.e., the side surface of the ultra-thin glass, may be vertical without any twists and turns, and may be ground so that the side surface roughness is constant. The ultra-thin glass ground in this manner may form an edge at the area where the top surface and the side surface are connected due to the grinding portion. The edge portion may be inclined or curved.
[0074] The ultra-thin glass may be manufactured by a manufacturing method described later, but is not limited thereto.
[0075] A method for manufacturing ultra-thin glass may include: cutting an original glass sheet into units; grinding the cut surfaces of the units; etching the ground units; and repairing the ground cut surfaces of the units.
[0076] In addition, the method for manufacturing the ultra-thin glass of the present invention may further include: cleaning; chemical strengthening; and / or chemical grinding after repairing.
[0077] Steps for cutting raw glass into units
[0078] First, a plurality of units are prepared by cutting a raw sheet of glass into units.
[0079] The step of cutting the original glass into cells is a step of forming the original glass into a shape that matches the design of the device to be used. The original glass can be cut to form a plurality of cells. This step can be performed without laminating the original glass into multiple layers. This brings the following advantages: cell tracking can be performed when defects occur, the manufacturing process can be simplified by omitting the lamination process, the defect rate due to residues that may occur in the lamination process can be reduced, and the shape of the glass side surface can be freely selected.
[0080] The cutting step is not particularly limited as long as the original glass can be cut to form a plurality of units. In one embodiment, the cutting step can use a diamond cutting wheel or a CNC cutting wheel with a laser to form a plurality of units presenting a certain shape.
[0081] Steps for grinding the cut surface of each unit
[0082] Next, the method of manufacturing ultra-thin glass includes grinding the cut surface of the unit.
[0083] The grinding is preferably physical grinding, and most preferably, the unit can be physically ground so that the cut surface of the unit has a circular shape. The cut surface of the unit refers to the side of the unit. At this time, the thickness of the cut unit can be the same as the thickness of the original glass.
[0084] Physical grinding includes physically grinding the chipping of the cut surface after the cutting step, while processing the side of the unit into a desired shape. At this time, the thickness of the cut unit can be the same as the thickness of the original glass before cutting.
[0085] From the perspective of stability to reduce the possibility of damage during post-processing, the ground cutting surface, ie, the side surface of the unit, may have a smooth circular shape with a predetermined curvature.
[0086] The physical grinding step is not particularly limited as long as it can physically grind the chipped edges generated during the cutting process. In one embodiment, the execution of the physical grinding step may include: a rough grinding step, in which the cut surface of the cut unit is ground using a grinding tool of 400 mesh or less; a medium grinding step, in which the cut surface of the unit after the rough grinding step is ground using a grinding tool of about 500 to 800 mesh; and a fine grinding step, in which the cut surface of the unit after the medium grinding step is ground using a grinding tool of 1200 mesh or more.
[0087] The step of etching the ground unit and repairing the ground cut surface of the ground unit Steps
[0088] Subsequently, the polished unit may be etched and the polished cut surface of the polished unit may be repaired. This step includes simultaneously performing the etching of the polished unit and the repairing of the polished cut surface of the polished unit. In addition, the repaired cut surface refers to the side surface of the finally manufactured ultra-thin glass unit.
[0089] In the repair step, the ground unit can be etched without a protective material such as a resin or film (used to prevent impact on the glass during the process or mask from etching liquid).
[0090] The ground unit can be made ultra-thin through a chemical etching process, and the ground cut surface of the unit can be repaired at the same time, thereby obtaining ultra-thin glass in units.
[0091] Specifically, the etching step of the ground unit may include but is not limited to chemical etching. The unit may be ultra-thinned by etching the ground unit.
[0092] Ultra-thinning refers to the process of reducing the thickness of glass to less than 100μm.
[0093] The etching of the grinded unit and the repair of the grinded cut surface of the grinded unit can be performed separately, but from the perspective of simplifying the process, it is more preferred to perform the repair of the cut surface of the grinded unit and the etching of the grinded unit simultaneously in the same way.
[0094] When etching and repairing are performed simultaneously, the aim is to make the thick film state unit ultra-thin while improving the edge strength of the cut unit, so that the repaired cut surface can be processed into a smoother round shape than the grinded cut surface. Repairing can eliminate defects such as chipping of the cut surface caused by physical grinding and reduce roughness, thereby suppressing damage caused by bending. The surface processed into a round shape preferably forms a smooth curve.
[0095] The chemical etching step may use an immersion method of immersing the unit in an etching solution, and in one embodiment, the execution of the chemical etching step may include at least one of the following steps: a unit fixture fixing step, in which the unit is fixed to a fixture for processing the unit; a fixture immersion step, in which the fixture is immersed in an etching solution tank filled with etching solution; a chemical etching step, in which the thickness and the cut surface are uniformly chemically etched at a constant etching rate under the immersion state; a fixture discharge step, in which when the chemical etching is completed, the fixture is discharged from the etching solution tank; and a unit separation step, in which the unit that has completed chemical etching in the fixture is separated.
[0096] In addition to the immersion method of completely immersing the unit in the etching solution, etching can also be assisted by further performing a side spray method or a top spray method. It is also possible to use only the side spray method or the top spray method without using the immersion method of completely immersing the unit in the etching solution. At this time, since the glass is cut into units, the surface tension of the sprayed etching solution causes the etching solution to be adsorbed to the surface of the glass unit, thereby achieving etching and side repair.
[0097] In the etching and repairing steps, etching and repairing can be performed while moving a plurality of glass units by upper and lower jigs, thereby minimizing contact between each glass unit.
[0098] In one or more embodiments, the etching solution may include one or more selected from the group consisting of hydrofluoric acid (HF), ammonium fluoride (NH4F), ammonium bifluoride (NH4HF2), sodium fluoride (NaF), sodium bifluoride (NaHF2), lithium fluoride (LiF), potassium fluoride (KF) and calcium fluoride (CaF2).
[0099] When etching of a ground unit and repairing of a ground cut surface of the ground unit are performed in separate steps, the unit can be etched by the chemical etching step as described above, and then the ground cut surface of the ground unit can be further repaired by the same method as the above-mentioned chemical etching step.
[0100] Cleaning, chemical strengthening and / or chemical polishing steps
[0101] In addition, the method for manufacturing ultra-thin glass may further include a cleaning step, a chemical strengthening step and / or a chemical grinding step. The order of the cleaning step, the chemical strengthening step and the chemical grinding step may be changed, added or omitted as needed.
[0102] The cleaning step may be to remove foreign matter and etching liquid remaining in the previous process. The cleaning process for removing the remaining foreign matter and etching liquid may be a common process. In one embodiment, cleaning is performed using a cleaning liquid, and a spray method of spraying the cleaning liquid or an immersion method of immersing in the cleaning liquid may be used.
[0103] The cleaning liquid is not particularly limited as long as it can clean the surface of the ultra-thin glass. In one or more embodiments, the cleaning liquid can be an alkaline cleaning liquid containing pure water (deionized water), potassium hydroxide (KOH) or sodium hydroxide (NaOH).
[0104] The chemical strengthening step is to immerse the ultra-thin glass in molten salt so that the alkali ions inside the ultra-thin glass are exchanged with the alkali ions in the molten salt, thereby strengthening the ultra-thin glass. In one embodiment, the chemical strengthening step may include: a preheating step of slowly heating the ultra-thin glass; chemically strengthening the preheated ultra-thin glass by ion exchange; and a step of slowly cooling the strengthened ultra-thin glass at room temperature.
[0105] The preheating step of slowly increasing the temperature of the ultra-thin glass can be used to slowly increase the temperature before immersing the ultra-thin glass in the ion exchange solution to prevent the ultra-thin glass from being damaged by rapid temperature changes during the chemical strengthening step performed at a high temperature of 350 to 500°C.
[0106] In the chemical strengthening step, when the Na + Glass with K + When the salt of ions comes into contact, the Na + With K + The exchange of ions proceeds inwards. At this time, K + Ions enter the ultra-thin glass structure Na + The position occupied by K + The ionic radius is larger than that of Na + The ionic radius of ions creates a compressive force around the network structure, which can strengthen the glass.
[0107] Replacement of K by chemical strengthening + The depth of the ions is not particularly limited, but may be 5% to 40% of the cell thickness from the viewpoint of improving bending resistance, and specifically preferably 10% to 35%, more preferably 15% to 30%.
[0108] In addition, the target depth of chemical strengthening may differ according to the glass thickness. For example, the depth (thickness) of chemical strengthening may differ according to the glass thickness as shown in Table 1 below.
[0109] [Table 1]
[0110]
[0111] The ion exchange solution used for chemical strengthening may be a commonly used ion exchange solution, and in one embodiment, it may contain potassium nitrate (KNO 3 ).
[0112] After the chemical strengthening process, a slow cooling step and a process of removing impurities may be further performed. The slow cooling and impurity removal processes may be common processes. In one embodiment, a cleaning process may be included after the process of contacting with external air for natural slow cooling to remove impurities, such as potassium nitrate.
[0113] In the chemical grinding step, the ultra-thin glass is ground using a chemical grinding solution. Therefore, from the perspective of improving bending resistance, the thickness of the ultra-thin glass after chemical grinding can be ground to a thickness of more than 80% and less than 100%, preferably more than 90% and less than 100%, of the thickness of the ultra-thin glass before chemical grinding.
[0114] The chemical polishing solution is not particularly limited as long as it is generally used in a process of polishing ultra-thin glass, but may include one or more of hydrofluoric acid (HF) and ammonium fluoride (NH 4 F).
[0115] In addition, after the chemical polishing step, a cleaning step may be further performed as needed.
[0116] A primer layer 120 is formed on a glass substrate 110 .
[0117] The primer layer 120 is used to further improve the adhesion between the glass substrate 110 and the substrate resin layer 130 .
[0118] In one embodiment of the present invention, the primer layer 120 may be formed of a primer layer-forming composition including at least one of a polyurethane resin and a polyester resin, and preferably may be formed of a primer layer-forming composition including a polyurethane resin.
[0119] In particular, from the perspective of preventing yellowing and improving hardness and bending resistance even under high temperature or ultraviolet conditions, the primer layer can be formed from a primer layer-forming composition comprising a water-dispersible polyurethane resin and a stabilizer, wherein the stabilizer can include a primary heat stabilizer and an auxiliary heat stabilizer.
[0120] Compared with general solvent-based polyurethane resins, water-dispersible polyurethane resins have the advantages of excellent optical properties and adhesion.
[0121] The water-dispersible polyurethane resin may include an ionic resin and a nonionic resin. The particle stability of the nonionic resin is good, but the mechanical properties such as film-forming property and adhesion are not as good as those of the water-dispersible polyurethane resin having an ionic functional group. Therefore, in order to maintain the mechanical properties, it is preferred to use a water-dispersible polyurethane resin having an ionic functional group.
[0122] The water-dispersible polyurethane resin can be manufactured by a prepolymer manufacturing process using polyester polyol, diisocyanate and chain extender as raw materials. Specifically, the water-dispersible polyurethane resin is prepared by mixing polyester polyol and diisocyanate and reacting at high temperature to prepare a prepolymer, then adding and dispersing the prepolymer in water with high-speed stirring, then adding a chain extender, and adjusting the molecular weight through the polymerization reaction of the dispersed prepolymer, thereby synthesizing the water-dispersible polyurethane resin.
[0123] In addition, when manufacturing a water-dispersible polyurethane resin with an ionic functional group, a dispersant (ionizing agent) is further added to the polyester polyol and the diisocyanate, and a hydrophilic prepolymer is generated by reaction at a high temperature. Then, a neutralizing agent is added to neutralize the hydrophilic prepolymer, and the neutralized hydrophilic prepolymer is added and dispersed in water with high-speed stirring. Then, a chain extender is added and the molecular weight is adjusted by the polymerization reaction of the dispersed hydrophilic prepolymer, thereby synthesizing a water-dispersible polyurethane resin.
[0124] The water-dispersible polyurethane resin specifically uses polycaprolactone polyol, which is a type of polyester polyol, to compensate for the disadvantage of being easily hydrolyzed by water, and has the advantage of being able to maintain adhesion without decomposition even under high temperature and high humidity. In addition, by using isophorone diisocyanate (as an aliphatic diisocyanate), it can exhibit transparent properties compared to aromatic diisocyanates.
[0125] The water-dispersible polyurethane resin contains no fluorine atoms and thus can maintain appropriate surface energy and provide adhesion to the film, and since it contains no sulfonic group, it can suppress the generation of haze and exhibit better optical properties.
[0126] The number average molecular weight of the water-dispersible polyurethane resin may be 10,000 to 4,000,000, preferably 20,000 to 2,000,000. When the number average molecular weight is within the above range, stability in a water-dispersible state can be ensured, coating properties are excellent, and mechanical properties are also good.
[0127] The content of the water-dispersible polyurethane resin may be 1% to 40% by weight based on 100% by weight of the total amount of the primer layer-forming composition, but is not limited thereto. When the content of the water-dispersible polyurethane resin is within the above content range, the adhesion between the glass substrate and the substrate resin layer is excellent and coating performance can be ensured.
[0128] Stabilizers include primary thermal stabilizers and secondary thermal stabilizers.
[0129] The stabilizer includes a combination of a primary heat stabilizer and an auxiliary heat stabilizer, thereby inhibiting further decomposition reaction by scavenging radicals generated by heat or ultraviolet rays, thereby preventing yellowing even under high temperature or ultraviolet conditions.
[0130] Specifically, by including a combination of a primary heat stabilizer and an auxiliary heat stabilizer as a stabilizer, yellowing does not occur even after a high temperature heat treatment of 100 to 250° C. for 20 to 60 minutes, thereby maintaining transparency.
[0131] Therefore, even after a high-temperature heat treatment performed when forming the base resin layer 130 described later, the primer layer 120 can maintain transparency without turning yellow.
[0132] For example, after the laminate having the primer layer 120 formed on the glass substrate 110 is heat-treated at 100 to 250° C. for 20 to 60 minutes, the yellowness index (YI) of the laminate according to ASTM E313-73 may be less than 1.0.
[0133] When the polymer material reacts with oxygen to cause decomposition reaction by heat or ultraviolet rays, the primary heat stabilizer prevents the chain reaction of free radicals by releasing its own hydrogen to stabilize the free radicals, thereby preventing yellowing by acting based on the free radical scavenging effect.
[0134] The primary heat stabilizer may be at least one selected from phenolic heat stabilizers and amine heat stabilizers.
[0135] For example, examples of phenolic heat stabilizers may include 3,9-bis[2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethoxy]-2,4,8,10-tetraoxospiro[5.5]undecane, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,3,5,-trimethyl-2,4,6,-tris(3'5'-di-tert-butyl-4-hydroxybenzyl)benzene, tri ... Glycol-bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl) propionate], 4,4'-thiobis(6-tert-butyl-3-methylphenol), tris-(3,5-di-tert-butyl-4-hydroxybenzyl)-isocyanurate, 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)-isocyanurate, 1,6-hexanediol-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], 2,2-thiobis(6-tert-butyl-3-methylphenol), -Diethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], N,N'-hexamethylene bis(3,5-di-tert-butyl-4-hydroxy-hydrocinnamic acid), 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, 2,4-bis[(octylthio)methyl]-o-cresol, 1,6-hexanediol-bis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], 3- (3,5-di-tert-butyl-4-hydroxyphenol) propionate octadecyl ester, 2,2'-methylenebis(4-methyl)-6-tert-butylphenol), 4,4'-butylene-bis(3-methyl-6-tert-butylphenol), 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-tris(4-hydroxybenzyl)benzene and tetrakis[methylene-3-(3,5'-di-tert-butyl-4'-hydroxyphenylpropionate)]methane, etc.
[0136] Examples of commercially available products of the phenolic heat stabilizer may include Irganox 1010 (manufactured by BASF), Sumilizer BBM-S (manufactured by Sumitomo Chemical), ADK STAB AO-80 (manufactured by ADEKA), Sumilizer GP (manufactured by Sumitomo Chemical), Irganox 1035 (manufactured by BASF), and the like.
[0137] For example, examples of amine heat stabilizers may include naphthylamine heat stabilizers such as 1-naphthylamine, phenyl-1-naphthylamine, p-octylphenyl-1-naphthylamine, p-nonylphenyl-1-naphthylamine, p-dodecylphenyl-1-naphthylamine and phenyl-2-naphthylamine; phenylenediamine heat stabilizers such as N,N'-diisopropyl-p-phenylenediamine, N,N'-diisobutyl-p-phenylenediamine, N,N'-diphenyl-p-phenylenediamine, N,N'-di-β-naphthyl-p-phenylenediamine, N-phenyl-N'-isopropyl-p-phenylenediamine, N-cyclohexyl-N'-phenyl-p-phenylenediamine, N-1,3-dimethylbutyl-N'-phenyl-p-phenylenediamine, dioctyl-p-phenylenediamine, phenylhexyl-p-phenylenediamine and phenyloctyl-p-phenylenediamine. p-phenylenediamine; diphenylamine heat stabilizers, such as dipyridylamine, diphenylamine, p-,p-'-di-n-butyldiphenylamine, p-,p-'-di-tert-butyldiphenylamine, p-,p-'-di-tert-amyldiphenylamine, p-,p-'-dioctyldiphenylamine, p-,p-'-dinonyldiphenylamine, p-,p-'-didecyldiphenylamine, p-,p-'-docosyldiphenylamine, p-,p-'-distyryldiphenylamine, p-,p-'-dimethoxydiphenylamine, 4,4'-bis(4-α,α-dimethylbenzoyl)diphenylamine, p-isopropoxydiphenylamine, dipyridylamine; and phenothiazine heat stabilizers, such as phenothiazine, N-methylphenothiazine, N-ethylphenothiazine, 3,7-dioctylphenothiazine, phenothiazine carboxylate and pheneselenazine.
[0138] The auxiliary heat stabilizer suppresses the generation of peroxide radicals by reducing peroxides generated by free radicals during the decomposition reaction, and produces a synergistic effect when used with the primary heat stabilizer to provide high-temperature heat resistance and prevent yellowing by preventing discoloration.
[0139] The second heat stabilizer may be at least one selected from a phosphorus-based heat stabilizer and a sulfur-based heat stabilizer.
[0140] For example, examples of phosphorus-based heat stabilizers may include 3,9-bis(2,6-di-tert-butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, diisodecyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, 2,2'-methylenebis(4,6-di-tert-butyl-1-phenoxy)(2-ethylhexyloxy)phosphite, 6- [3-(3-tert-butyl-4-hydroxy-5-methylphenyl) propoxy]-2,4,8,10-tetra-tert-butyl dibenzo[d,f][1,3,2]dioxaphosphine, triphenyl phosphite, diphenyl isodecyl phosphite, phenyl diisodecyl phosphite, 4,4'-butylene-bis(3-methyl-6-tert-butylphenyl tricosyl) phosphite, octadecyl phosphite, tris(nonylphenyl) phosphite, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-(3,5-di-tert-butyl-4-hydroxybenzyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-decyloxy-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, tris(2,4-di-tert-butylphenyl)phosphite, cycloneopentanatetraylbis(2,4-di-tert-butyl) phenyl) phosphite, cyclic neopentane tetrayl bis(2,6-di-tert-butylphenyl) phosphite, 2,2-methylenebis(4,6-di-tert-butylphenyl) octyl phosphite, tris(2,4-di-tert-butylphenyl) phosphite, tetrakis(2,4-di-tert-butylphenyl)[1,1-biphenyl]-4,4'-diyl diphosphite, bis[2,4-bis(1,1-dimethylethyl)-6-methylphenyl]ethyl phosphonic acid, etc.
[0141] Examples of commercially available products of the phosphorus-based heat stabilizer may include: ADK STAB 1178, ADK STAB TPP, ADK STAB 1500, ADK STAB 135A, ADK STAB 517 from Adeka Corporation; Sumilizer GP from Sumitomo Chemical; and Irganox 1035 from BASF, and the like.
[0142] For example, examples of sulfur-based heat stabilizers may include 2,2-bis({[3-(dodecylthio)propionyl]oxy}methyl)-1,3-propanediyl-bis[3-(dodecylthio)propionate], 2-mercaptobenzimidazole, dilauryl 3,3'-thiodipropionate, dimyristyl 3,3'-thiodipropionate, distearyl 3,3'-thiodipropionate, pentaerythritol tetrakis(3-laurylthiopropionate), 2-mercaptobenzimidazole, and the like.
[0143] The content of the stabilizer may be 0.1 to 10% by weight based on 100% by weight of the total amount of the primer layer-forming composition, but is not limited thereto. When the content of the stabilizer is within the above content range, the surface of the cured film can be prevented from being decomposed by heat or ultraviolet rays without impairing optical properties, and has the advantage of not affecting curability during thermal curing.
[0144] The primer layer-forming composition of the present invention may further contain a leveling agent.
[0145] The purpose of adding the leveling agent is to improve the smoothness and coating properties of the coating film when the composition is applied, and the leveling agent may include one or more of a silicone leveling agent, a fluorine leveling agent, and an acrylic leveling agent.
[0146] Specifically, examples of leveling agents may include, but are not limited to, BYK-306, BYK-307, BYK-323, BYK-331, BYK-333, BYK-337, BYK-373, BYK-375, BYK-377, BYK-378, BYK-3530, BYK-3560, BYK-358N, BYK-361N from BYK-chemi; TEGO Glide 410, TEGO Glide 411, TEGOGlide 415, TEGO Glide 420, TEGO Glide 432, TEGO Glide 435, TEGO Glide 440, TEGOGlide 450, TEGO Glide 455, TEGO Rad 2100, TEGO Rad 2200N, TEGO Rad 2200N from TEGO; 2250, TEGO Rad2300, TEGO Rad 2500; and FC-4430, FC-4432 from 3M, etc.
[0147] The content of the leveling agent may be 0.01 to 1 wt % based on 100 wt % of the total amount of the primer layer-forming composition, but is not limited thereto. However, when the content of the leveling agent is within the above content range, it has the advantage of maximizing the smoothness and coating performance of the coating film while maintaining excellent hardness and flexibility.
[0148] The primer layer-forming composition of the present invention may further contain a solvent.
[0149] The solvent used is not particularly limited as long as it can dissolve or disperse the above components.
[0150] The solvent that can be used may preferably be alcohols (methanol, ethanol, isopropanol, butanol, methyl cellosolve, ethyl cellosolve, etc.), ketones (methyl ethyl ketone, methyl butyl ketone, methyl isobutyl ketone, diethyl ketone, dipropyl ketone, cyclohexanone, etc.), acetates (ethyl acetate, propyl acetate, n-butyl acetate, tert-butyl acetate, methyl cellosolve acetate, ethyl cellosolve acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, methoxybutyl acetate, methoxypentyl acetate, etc.), hexanes (hexane, heptane, octane, etc.), benzenes (benzene, toluene, xylene, etc.), ethers (diglyme, diglyme, diethyl ether, diglyme dipropyl ether, diglyme dibutyl ether, propylene glycol monomethyl ether, etc.), etc. The above-exemplified solvents may be used alone or in combination of two or more.
[0151] The solvent can be included with the residual amount so that the total amount of the primer layer forming composition as a whole is 100 weight %. For example, in the primer layer forming composition total amount as 100 weight %, the consumption of the solvent can be 50 weight % to 98 weight %. If the content of the solvent is less than the above content, the viscosity is high, which not only reduces the processability, but also makes it impossible to reduce the thickness of the coating, which may cause flexibility to reduce. On the contrary, if it exceeds the above scope, the required film thickness can not be formed, and the coating fluid may flow down in the drying process, pollute the opposite side of the glass or film, and cause stains.
[0152] The primer layer 120 can be formed by applying the primer layer-forming composition on the glass substrate 110 and curing the composition.
[0153] Coating can be carried out by known methods such as slit coating, doctor blade coating, spin coating, casting, micro-gravure coating, gravure coating, rod coating, roller coating, wire rod coating, dip coating, spray coating, screen printing, gravure printing, flexographic printing, offset printing, inkjet coating, dispenser printing, nozzle coating and capillary coating.
[0154] Curing can be performed by pre-bake and / or post-bake thermal curing process. The thermal curing process can be performed by known methods, preferably in an oven at 80 to 150° C. for 1 to 5 minutes.
[0155] The primer layer may be formed by further adding a photocurable oligomer and / or monomer and a photoinitiator and further performing a photocuring process. In the case of photocuring, it is preferred that the cumulative amount of irradiation after drying is 300 to 1000 mJ / cm 2 UV rays to form a primer layer.
[0156] The thickness of the primer layer may be 0.1 μm or more and less than 10 μm, preferably 0.1 μm to 2 μm. When the thickness of the primer layer is within the above range, it is advantageous in terms of adhesion to the glass substrate. If the thickness of the primer layer is less than 0.1 μm, when the substrate resin layer is coated on the primer layer, it may be difficult to penetrate the primer layer and exhibit adhesion, and if the thickness of the primer layer is 10 μm or more, the optical properties may be reduced.
[0157] The base resin layer 130 is formed on the primer layer 120 .
[0158] The base resin layer 130 is used to support a functional coating layer 140 to be described later, and serves as a protective layer to prevent scattering of the glass base 110. In addition, the base resin layer 130 is used to control bending resistance, pencil hardness, and curling characteristics of the optical laminate.
[0159] In one embodiment of the present invention, the base resin layer may be formed of a base resin layer forming composition containing at least one of a polyimide resin and a polyamideimide resin, from the viewpoint of being more easily applied to a flexible display due to excellent durability against repeated bending while ensuring pencil hardness and curling characteristics. In particular, from the viewpoint of bending resistance, pencil hardness and curling characteristics, the base resin layer may be formed of a base resin layer forming composition containing a polyamideimide resin.
[0160] The polyimide resin refers to a resin including a repeating unit containing an imide group.
[0161] The polyimide resin can be produced by imidizing a polyamic acid obtained by polycondensation of a tetracarboxylic acid compound and a diamine compound. The imidization can be performed chemically and / or thermally.
[0162] Tetracarboxylic acid compound represents tetracarboxylic acid or tetracarboxylic acid derivative.The example of tetracarboxylic acid derivative can include the anhydride (preferably dianhydride) and acyl chloride of tetracarboxylic acid.The example of tetracarboxylic acid compound can include the aliphatic tetracarboxylic acid compound such as aromatic tetracarboxylic acid and its anhydride (preferably its dianhydride) and aliphatic tetracarboxylic acid and its anhydride (preferably its dianhydride).These tetracarboxylic acid compounds can be used alone or in combination of two or more.
[0163] Specific examples of the aromatic tetracarboxylic dianhydride may include 4,4'-oxydiphthalic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, 2,2-bis(3,4-dicarboxyphenoxyphenyl)propane dianhydride, 4,4'-(hexafluoroisopropyl)propane 1,2-bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,2-bis(3,4-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, 4,4'-(phenylenedioxy)diphthalic dianhydride, 4,4'-(isophenylenedioxy)diphthalic dianhydride, 1,2,4,5-benzenetetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, and the like.
[0164] Examples of the aliphatic tetracarboxylic dianhydride may include 1,2,4,5-cyclohexanetetracarboxylic dianhydride, 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride, bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, dicyclohexyl-3,3′,4,4′-tetracarboxylic dianhydride, 1,2,3,4-butanetetracarboxylic dianhydride, 1,2,3,4-pentanetetracarboxylic dianhydride, and the like.
[0165] As the diamine compound, an aliphatic diamine and / or an aromatic diamine can be used.
[0166] Examples of the aliphatic diamine may include hexamethylenediamine, 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, norbornanediamine, 4,4′-diaminodicyclohexylmethane, and the like.
[0167] Examples of the aromatic diamines may include p-phenylenediamine, m-phenylenediamine, 2,4-toluenediamine, m-phenylenediamine, p-phenylenediamine, 1,5-diaminonaphthalene, 2,6-diaminonaphthalene, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylpropane, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, bis(4-( 4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy))phenyl)sulfone, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 2,2-bis(4-(3-aminophenoxy)phenyl)propane, 2,2'-dimethylbenzidine, 2,2'-bis(trifluoromethyl)benzidine, 4,4'-bis(4-aminophenoxy)biphenyl, 9,9-bis(4-aminophenyl)fluorene, 9,9-bis(4-amino-3-methylphenyl)fluorene, 9,9-bis(4-amino-3-chlorophenyl)fluorene and 9,9-bis(4-amino-3-fluorophenyl)fluorene.
[0168] The molar ratio of the tetracarboxylic acid compound and the diamine compound may be adjusted to control the elastic modulus of the substrate resin layer within the above range.
[0169] The weight average molecular weight (Mw) of the polyimide resin may be 100,000 to 1,000,000 based on standard polystyrene. If the weight average molecular weight (Mw) of the polyimide resin is within the above range, coating performance can be ensured when forming a coating film, and the bending resistance, pencil hardness and curling characteristics of the optical laminate are better.
[0170] The polyamide-imide resin refers to a resin containing a repeating unit containing an imide group and a repeating unit containing an amide group.
[0171] The polyamide-imide resin can be produced by imidizing a polyamic acid obtained by polycondensation of a tetracarboxylic acid compound, a dicarboxylic acid compound, and a diamine compound. The imidization can be performed chemically and / or thermally.
[0172] The tetracarboxylic acid compound and the diamine compound may be the same as those used in producing the polyimide resin.
[0173] The dicarboxylic acid compound may refer to a dicarboxylic acid or a dicarboxylic acid derivative, and examples of the dicarboxylic acid derivative may include acid chlorides and esters of dicarboxylic acids. The dicarboxylic acid compound may be used alone or in combination of two or more.
[0174] Specific examples of the dicarboxylic acid compound may include 2,5-thiophenedicarboxylic acid, 1,3-cyclobutanedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 4,4′-oxybis(benzoyl chloride) (OBBC), terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 4,4′-biphenyldicarboxylic acid, 3,3′-biphenyldicarboxylic acid, terephthaloyl chloride (TPC), 4,4′-biphenyldicarboxylic acid chloride (BPDOC), 4,4′-oxybis(benzoyl chloride) (OBBC), and the like.
[0175] The molar ratio of the tetracarboxylic acid compound, the dicarboxylic acid compound, and the diamine compound may be adjusted so as to control the elastic modulus of the base resin layer within the above range.
[0176] The weight average molecular weight (Mw) of the polyamideimide resin may be 100,000 to 1,000,000 based on standard polystyrene. If the weight average molecular weight (Mw) of the polyamideimide resin is within the above range, coating properties when forming a coating film can be ensured, and the bending resistance, pencil hardness, and curling properties of the optical laminate are better.
[0177] The base resin layer-forming composition may further contain additives such as an ultraviolet absorber, inorganic particles, a surfactant, and an adhesion improver, if necessary.
[0178] The base resin layer forming composition of the present invention may further contain a solvent.
[0179] The solvent used is not particularly limited as long as it can dissolve or disperse the above components.
[0180] Examples of solvents that can be used may include alcohol solvents (methanol, ethanol, isopropanol, butanol, methyl cellosolve, ethyl cellosolve, etc.), organic solvents containing nitrogen atoms (N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, hexamethylphosphoramide, 1,3-dimethyl-2-imidazolidinone, etc.), γ-butyrolactone, etc. The above-exemplified solvents may be used alone or in combination of two or more.
[0181] The solvent may be contained in a residual amount such that the total amount of the base resin layer forming composition is 100 wt %. For example, the amount of the solvent used may be an amount to adjust the viscosity of the composition to a desired range to ensure coating performance.
[0182] The base resin layer 130 can be formed by applying the base resin layer forming composition on the primer layer 120 and curing the composition.
[0183] Coating can be carried out by known methods such as slot coating, knife coating, spin coating, casting, micro gravure coating, gravure coating, rod coating, roller coating, wire rod coating, dip coating, spray coating, screen printing, gravure printing, flexographic printing, offset printing, inkjet coating, dispenser printing, nozzle coating and capillary coating.
[0184] Curing can be performed by pre-bake and / or post-bake thermal curing process. The thermal curing process can be performed by a known method, and can be performed using an oven.
[0185] Pre-baking is preferably performed at a temperature below 140°C. When the substrate resin is a polyimide resin, post-baking is preferably performed at a temperature above 200°C. When the substrate resin is a polyimide resin, post-baking is preferably performed at a temperature above 150°C.
[0186] From the perspective of the pencil hardness of the optical laminate, the thickness of the substrate resin layer may be 3 μm to 50 μm, preferably 5 μm to 30 μm, and more preferably 5 μm to 10 μm. If the thickness of the substrate resin layer is thinner than the above range, the protective ability of the glass is reduced and the glass is easily broken during handling. If the thickness of the substrate resin layer is thicker than the above range, curling that occurs when the substrate resin layer is dried may become a problem.
[0187] The functional coating layer 140 is formed on the base resin layer 130 .
[0188] The functional coating 140 is used to improve the surface hardness. In addition, the functional coating 140 can show antifouling performance, excellent wear resistance, excellent elastic recovery rate and excellent resistance to pen pressure, and provide excellent effects in durability such as scratch resistance, chemical resistance and bending resistance. In addition, the functional coating 140 controls the bending resistance and curling characteristics of the optical laminate.
[0189] The functional coating 140 may be a hard coating.
[0190] In one embodiment of the present invention, the hard coating layer may be formed of a hard coating composition including a light-transmitting resin, a fluorine-based UV-curable functional group-containing compound, a photoinitiator, and a solvent.
[0191] The light-transmitting resin is a photocurable resin, and the photocurable resin may include but is not limited to photocurable (meth)acrylate oligomers and / or monomers.
[0192] Examples of the photocurable (meth)acrylate oligomer may include epoxy (meth)acrylate, urethane (meth)acrylate, polyhedral oligomeric silsesquioxane (meth)acrylate, dendritic (meth)acrylate, etc., and at least one of urethane (meth)acrylate and dendritic (meth)acrylate is preferred.
[0193] Urethane (meth) acrylate can be produced by reacting a (meth) acrylate having a hydroxyl group in the molecule with a compound having an isocyanate group in the presence of a catalyst. Specific examples of (meth) acrylate having a hydroxyl group in the molecule may include 2-hydroxyethyl (meth) acrylate, 2-hydroxyisopropyl (meth) acrylate, 4-hydroxybutyl (meth) acrylate, caprolactone ring-opening hydroxy acrylate, pentaerythritol tri(meth) acrylate, dipentaerythritol penta(meth) acrylate, and the like. In addition, specific examples of the compound having an isocyanate group may include 1,4-diisocyanatobutane, 1,6-diisocyanatohexane, 1,8-diisocyanatooctane, 1,12-diisocyanatododecane, 1,5-diisocyanato-2-methylpentane, trimethyl-1,6-diisocyanatohexane, 1,3-bis(isocyanatomethyl)cyclohexane, trans-1,4-cyclohexene diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), isophorone diisocyanate, Isocyanates, toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, xylene-1,4-diisocyanate, tetramethylxylene-1,3-diisocyanate, 1-chloromethyl-2,4-diisocyanate, 4,4'-methylenebis(2,6-dimethylphenylisocyanate), 4,4'-oxybis(phenylisocyanate), trifunctional isocyanates derived from hexamethylene diisocyanate, trimethylolpropane adduct toluene diisocyanate, etc.
[0194] Dendritic (meth)acrylate refers to a (meth)acrylate oligomer having a dendritic structure, where "dendritic structure" refers to a polymerized shape in which monomers radially branch from a core and spread radially. (Meth)acrylate is not limited thereto, and any (meth)acrylate may be used as long as it is in the above-mentioned form.
[0195] Examples of commercially available products of dendritic (meth)acrylates may include: Miramer SP1106 from Miwon; and Viscoat 1000, Viscoat 1020, and Viscoat 1080 from Osaka Organic.
[0196] The monomer may be any commonly used monomer without limitation, and preferably has an unsaturated group (such as (meth)acryloyl, vinyl, styryl and allyl) as a photocurable functional group in the molecule, among which a monomer having a (meth)acryloyl group is preferred.
[0197] Specific examples of the monomer having a (meth)acryloyl group may be at least one selected from the group consisting of neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, propylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, 1,2,4-cyclohexane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, isooctyl (meth)acrylate, isohexyl (meth)acrylate, stearyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, phenoxyethyl (meth)acrylate and isobornyl (meth)acrylate.
[0198] The photocurable (meth)acrylate oligomers and monomers exemplified above may be used alone or in combination of two or more.
[0199] The content of the light-transmitting resin may be 1 to 80 wt % based on 100 wt % of the total amount of the hard coating composition. If the content of the light-transmitting resin is less than 1 wt %, it is difficult to sufficiently increase the hardness, and if it exceeds 80 wt %, curling becomes more serious.
[0200] The fluorine-based UV-curable functional group-containing compound is a component that imparts antifouling properties, abrasion resistance, and chemical resistance. The fluorine-based UV-curable functional group-containing compound is not particularly limited as long as it contains fluorine and can chemically bond with the light-transmitting resin of the matrix forming the hard coating layer due to the ultraviolet curing functional group.
[0201] The fluorine-based UV-curable functional group-containing compound may use at least one selected from the group consisting of a perfluoroalkyl-containing (meth)acrylate, a perfluoropolyether-containing (meth)acrylate, a perfluorocyclic aliphatic-containing (meth)acrylate, and a perfluoroaromatic-containing (meth)acrylate. In this case, it has excellent antifouling properties and forms a chemical bond with the hard coating layer, maintaining the antifouling properties even after repeated use because it has the advantage of long-term durability.
[0202] The fluorine-based UV-curable functional group-containing compound preferably has 1 to 6 UV-curable functional groups.
[0203] Examples of the fluorine-based UV-curable functional group-containing compound may include 2,2,2-trifluoroethyl acrylate, 2,2,3,3,3-pentafluoropropyl acrylate, 2-perfluorobutylethyl acrylate, 3-perfluorobutyl-2-hydroxypropyl acrylate, 2-perfluorohexylethyl acrylate, 3-perfluorohexyl-2-hydroxypropyl acrylate, 2-perfluorooctylethyl acrylate, 3-perfluorooctyl-2-hydroxypropyl acrylate, 2-perfluorodecylethyl ... -3-Methylbutyl Ethyl Acrylate, 3-Perfluoro-3-Methoxybutyl-2-Hydroxypropyl Acrylate, 2-Perfluoro-5-Methylhexyl Ethyl Acrylate, 3-Perfluoro-5-Methylhexyl-2-Hydroxypropyl Acrylate, 2-Perfluoro-7-Methyloctyl-2-Hydroxypropyl Acrylate, Tetrafluoropropyl Acrylate, Octafluoropentyl Acrylate, Dodecafluoroheptyl Acrylate, Hexafluorononyl Acrylate, Hexafluorobutyl Acrylate, 2,2,2-Trifluoroethyl Methacrylate, 2, 2,3,3,3-pentafluoropropyl methacrylate, 2-perfluorobutyl ethyl methacrylate, 3-perfluorobutyl-2-hydroxypropyl methacrylate, 2-perfluorooctyl ethyl methacrylate, 3-perfluorooctyl-2-hydroxypropyl methacrylate, 2-perfluorodecyl ethyl methacrylate, 2-perfluoro-3-methylbutyl ethyl methacrylate, 3-perfluoro-3-methylbutyl-2-hydroxypropyl methacrylate, 2-perfluoro-5-methylhexyl ethyl methacrylate, methyl acrylate 3-perfluoro-5-methylhexyl-2-hydroxypropyl methacrylate, 2-perfluoro-7-methyloctyl ethyl methacrylate, 3-perfluoro-6-methyloctyl methacrylate, tetrafluoropropyl methacrylate, octafluoropentyl methacrylate, octafluoropentyl methacrylate, dodecafluoroheptyl methacrylate, hexafluorononyl methacrylate, 1-trifluoromethyl trifluoroethyl methacrylate, hexafluorobutyl methacrylate, triacryloyl-heptadecafluorononenyl-pentaerythritol, etc.
[0204] Commercially available examples of the fluorine-based UV-curable functional group-containing compound may include KY-1203 (Shin-Etsu Corporation), OPTOOL DAC-HP (DAIKIN Corporation), UVAS-2003 (Sooyang Chemtec Corporation), and the like.
[0205] The content of the fluorine-based UV-curable functional group-containing compound may be greater than 0.01% by weight and less than 10% by weight, based on the total amount of the hard coating composition as 100% by weight. When the content of the fluorine-based UV-curable functional group-containing compound is within the above range, it is preferred because excellent wear resistance and antifouling effects can be imparted. If the content of the fluorine-based UV-curable functional group-containing compound is less than the above range, it may be difficult to fully achieve wear resistance or antifouling, and if it exceeds the above range, it may be difficult to fully achieve hardness and / or scratch resistance may be reduced.
[0206] In one embodiment of the present invention, a photoinitiator is included to initiate photocuring of the hard coating composition, and may include, for example, a photo radical initiator capable of forming radicals by light irradiation.
[0207] Examples of the photoinitiator may include a type 1 initiator that generates free radicals by molecular decomposition due to a difference in chemical structure or molecular bond energy, and a type 2 initiator that coexists with a tertiary amine to induce hydrogen recapture.
[0208] For example, examples of type 1 initiators may include: acetophenones, such as 4-phenoxydichloroacetophenone, 4-tert-butyldichloroacetophenone, 4-tert-butyltrichloroacetophenone, diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropane-1-one, 1-(4-dodecylphenyl)-2-hydroxy-2-methylpropane-1-one, 4-(2-hydroxyethoxy)-phenyl(2-hydroxy-2-propyl)ketone and 1-hydroxycyclohexylphenylketone, etc.; benzoins, such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzyl dimethyl ketal, etc.; phosphine oxides; and titanocene compounds, etc.
[0209] For example, examples of type 2 initiators may include: benzophenones, such as benzophenone, benzoylbenzoic acid, benzoylbenzoic acid methyl ether, 4-phenylbenzophenone, hydroxybenzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, 3,3'-methyl-4-methoxybenzophenone, etc.; and thioxanthones, such as thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, etc.
[0210] The above-mentioned photopolymerization initiators may be used alone or in combination of two or more. In addition, type 1 and type 2 initiators may be used alone or in combination.
[0211] The content of the photoinitiator may be about 0.1 to 10 wt %, preferably about 1 to 5 wt %, based on 100 wt % of the total amount of the hard coating composition. If the content of the photoinitiator is less than 0.1 wt %, sufficient curing may not be performed, and the mechanical properties and adhesion of the hard coating film or hard coating may not be ensured. If the content of the photoinitiator exceeds 10 wt %, poor adhesion, cracks, and curling may occur due to shrinkage during curing.
[0212] The solvent can be used without limitation as long as it is known in the art that it can dissolve or disperse the above composition. In addition, the solvent is used to provide time for the fluorine-based UV-curable functional group-containing compound to float to the outermost surface of the coating due to the difference in surface tension during the process of applying the hard coating composition on the substrate and drying it.
[0213] Examples of the solvent that can be used preferably include alcohols (methanol, ethanol, isopropanol, butanol, methyl cellosolve, ethyl cellosolve, etc.), ketones (methyl ethyl ketone, methyl butyl ketone, methyl isobutyl ketone, diethyl ketone, dipropyl ketone, cyclohexanone, etc.), acetates (ethyl acetate, propyl acetate, n-butyl acetate, tert-butyl acetate, methyl cellosolve acetate, ethyl cellosolve acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, methoxybutyl acetate, methoxypentyl acetate, etc.), hexanes (hexane, heptane, octane, etc.), benzenes (benzene, toluene, xylene, etc.), ethers (diglyme, diglyme, diethyl ether, diglyme dipropyl ether, diglyme dibutyl ether, propylene glycol monomethyl ether, etc.), etc. The above-exemplified solvents can be used alone or in combination of two or more.
[0214] Preferably, a good solvent alone or a mixed solvent containing a good solvent and a poor solvent is used as the solvent. The good solvent and the poor solvent can be appropriately selected according to the material of the transparent film used as the base film.
[0215] The content of the solvent may be 10 to 95% by weight based on 100% by weight of the total amount of the hard coating composition. If the content of the solvent is less than the above content, the viscosity is high, which not only reduces the workability but also makes it impossible to fully swell the substrate. On the contrary, if it exceeds the above range, the drying process requires more time and the economic efficiency is poor, and haze may be generated due to severe swelling of the base film, so it is necessary to use it appropriately within the above range.
[0216] The hard coating composition may further contain inorganic particles.
[0217] The inorganic particles may be inorganic nanoparticles and are components added to increase the elastic recovery rate of the hard coat layer.
[0218] Specifically, when the hard coating composition contains inorganic nanoparticles, there is an advantage that mechanical properties can be further improved. More specifically, inorganic nanoparticles have an advantage of being uniformly distributed in the coating film to improve mechanical properties such as pen pressure and pencil hardness.
[0219] The inorganic nanoparticles may have an average particle size of 1 to 100 nm, specifically 1 to 80 nm, more specifically 5 to 50 nm. When the average particle size of the inorganic nanoparticles satisfies the above range, there is an advantage that a uniform coating can be formed by preventing coagulation in the composition. In addition, the problem of degradation of the optical properties and mechanical properties of the coating can be prevented.
[0220] The inorganic nanoparticles may include one or more of the group consisting of Al2O3, SiO2, ZnO, ZrO2, BaTiO3, TiO2, Ta2O5, Ti3O5, ITO, IZO, ATO, ZnO-Al, Nb2O3, SnO and MgO, but are not limited thereto. However, it may include metal oxides commonly used in the art.
[0221] Specifically, the inorganic nanoparticles may be Al2O3, SiO2 and / or ZrO2. The inorganic nanoparticles may be directly manufactured or commercially available. In the case of commercially available products, inorganic nanoparticles dispersed in an organic solvent at a concentration of 10 to 80 wt% may be used.
[0222] The hard coating composition may further include a leveling agent to provide smoothness and coatability to the coating film when the composition is applied.
[0223] The leveling agent can be a commercially available silicone leveling agent, fluorine leveling agent, or acrylic polymer leveling agent, such as BYK-306, BYK-307, BYK-323, BYK-331, BYK-333, BYK-337, BYK-373, BYK-375, BYK-377, BYK-378, BYK-3530, BYK-3560, BYK-358N, BYK-361N from BYK-chemi; TEGO Glide 410, TEGO Glide 411, TEGO Glide 415, TEGO Glide 420, TEGO Glide 432, TEGO Glide 435, TEGO Glide 440, TEGO Glide 450, TEGO Glide 455, TEGO Rad from TEGO. 2100, TEGO Rad2200N, TEGO Rad 2250, TEGO Rad 2300, TEGO Rad 2500; and FC-4430, FC-4432 from 3M Company, etc. Based on 100% by weight of the total amount of the hard coating composition, the content of the leveling agent may be 0.1 to 1% by weight.
[0224] In addition to the above-mentioned components, the hard coating composition may further include components commonly used in the art, such as an ultraviolet stabilizer, a heat stabilizer, an antioxidant, a lubricant, and an antifouling agent.
[0225] UV stabilizers are additives added to protect the coating film by blocking or absorbing UV rays, because the surface of the cured coating film decomposes due to continuous exposure to UV rays, resulting in discoloration and embrittlement. UV stabilizers are divided into absorbers, quenchers, and hindered amine light stabilizers (HALS) according to their mechanism of action. In addition, they can be divided into phenyl salicylate (absorber), benzophenone (absorber), benzotriazole (absorber), nickel derivatives (quencher), free radical scavengers, etc. according to the chemical structure. There is no particular limitation on the UV stabilizer as long as it does not significantly change the initial color of the coating film.
[0226] In addition, the heat stabilizer is a commercially available product, and polyphenols as a main heat stabilizer and phosphites and lactones as an auxiliary heat stabilizer may be used alone or in combination.
[0227] The content of the UV stabilizer and the heat stabilizer can be appropriately adjusted to a level that does not affect the UV curing performance.
[0228] The hard coat layer can be formed by applying the hard coat composition on the base resin layer, drying it, and then UV curing it.
[0229] The hard coating composition can be applied onto the base resin layer by a known method such as a die coater, an air knife, a reverse roll, a spray, a doctor blade, casting, gravure printing, micro gravure printing, or spin coating.
[0230] After applying the hard coating composition to the substrate resin layer, the volatile matter is evaporated at a temperature of 30 to 150° C. to dry for 10 seconds to 1 hour, more specifically 30 seconds to 30 minutes, and then cured by irradiation with UV light. The irradiation amount of UV light can be specifically about 0.01 to 10 J / cm 2 , and more specifically may be 0.1 to 2 J / cm 2 .
[0231] At this time, the thickness of the hard coating layer may be specifically 1 μm to 10 μm, more specifically 3 μm to 10 μm. When the thickness of the hard coating layer is within the above range, excellent hardness, bending resistance, and curling characteristics may be obtained.
[0232] One embodiment of the present invention relates to an image display device having the above-mentioned optical laminate. For example, the optical laminate of the present invention can be used as a window in an image display device (particularly a flexible display, a foldable display, a rollable display or a stretchable display). In addition, the optical laminate of the present invention can also be used by attaching it to a polarizing plate, a touch sensor, etc.
[0233] The optical laminate according to one embodiment of the present invention can be used for LCDs of various driving types, such as reflective, transmissive and transflective LCDs, or TN, STN, OCB, HAN, VA and IPS types. In addition, the optical laminate according to one embodiment of the present invention can be used for various image display devices, such as plasma displays, field emission displays, organic EL displays, inorganic EL displays and electronic paper.
[0234] One embodiment of the present invention relates to a variable-transmittance optical layered body having the above-mentioned optical layered body.
[0235] The variable transmittance optical stack has a stacked structure in which a polarizing plate and a liquid crystal layer are disposed inside and transparent members are disposed outside on both sides to protect the polarizing plate and the liquid crystal layer. The variable transmittance optical stack according to the present invention uses the above optical stack as a transparent member.
[0236] In addition, one embodiment of the present invention relates to a smart window including a variable transmittance optical stack.
[0237] The smart window may be applied to at least one of a front window, a rear window, a side window, a skylight, and an interior partition of a car, or may be applied to a building window.
[0238] Below, the present invention will be described in more detail by examples, comparative examples and experimental examples. These examples, comparative examples and experimental examples are only used to illustrate the present invention, and it is obvious to those skilled in the art that the scope of the present invention is not limited thereto.
[0239] Preparation Example 1: Preparation of a primer layer-forming composition
[0240] 22.67 wt% of a water-dispersible polyurethane (hereinafter referred to as PUD) (T&L Company, Akuarane 3410, solid content 30 wt%), 77.08 wt% of ethanol and 0.1% of a silicone leveling agent (BYK Company, BYK-333) were diluted with a mixer, and then 0.075 wt% of a primary stabilizer (STAB AO-80, Adeka Company) and 0.075 wt% of an auxiliary stabilizer (STAB 135A, Adeka Company) were added and stirred to prepare a composition for forming a primer layer.
[0241] Preparation Example 2-1: Preparation of a composition for forming a base resin layer
[0242] Under a nitrogen atmosphere, 14.67 g (45.8 mmol) of 2,2'-bis(trifluoromethyl)benzidine (TFMB) and 233.3 g of N,N-dimethylacetamide (DMAc) adjusted to a moisture content of 200 ppm were added to a 1L separable flask with a stirring paddle, and TFMB was dissolved in DMAc while stirring at room temperature. Next, 4.283 g (13.8 mmol) of 4,4'-oxydiphthalic anhydride (OPDA) was added to the flask and stirred at room temperature for 16.5 hours. Then, 1.359 g (4.61 mmol) of 4,4'-oxybis(benzoyl chloride) (OBBC) and 5.609 g (27.6 mmol) of terephthaloyl chloride (TPC) were added to the flask and stirred at room temperature for 1 hour. Next, 4.937 g (48.35 mmol) of acetic anhydride and 1.501 g (16.12 mmol) of 4-methylpyridine were added to the flask, stirred at room temperature for 30 minutes, heated to 70° C. using an oil bath, and stirred for further 3 hours to obtain a reaction solution.
[0243] After the obtained reaction solution was cooled to room temperature, 360 g of methanol and 170 g of ion exchange water were added to obtain a precipitate of polyamide-imide. The precipitate was immersed in methanol for 12 hours, filtered and recovered, and washed with methanol. Next, the precipitate was dried under reduced pressure at 100° C. to obtain a polyamide-imide resin.
[0244] N,N-dimethylacetamide (DMAc) was added to the obtained polyamideimide resin to a concentration of 15% by weight to prepare a composition for forming a base resin layer.
[0245] Preparation Example 2-2: Preparation of a composition for forming a base resin layer
[0246] Under a nitrogen atmosphere, 45 g (140.5 mmol) of 2,2'-bis(trifluoromethyl)benzidine (TFMB) and 600.9 g of N,N-dimethylacetamide (DMAc) adjusted to a moisture content of 200 ppm were added to a 1 L separable flask with a stirring paddle, and TFMB was dissolved in DMAc while stirring at room temperature. Next, 4.14 g (14.1 mmol) of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) was added to the flask, stirred at room temperature for 2.5 hours, and then 25.01 g (56.3 mmol) of 4,4'-(hexafluoroisopropylidene)diphthalic dianhydride (6FDA) was added, and stirred at room temperature for 15 hours. Then, 4.15 g (14.1 mmol) of 4,4'-oxybis(benzoyl chloride) (OBBC) and 11.43 g (56.3 mmol) of terephthaloyl chloride (TPC) were added to the flask, and stirred at room temperature for 1 hour. Next, 21.55 g (211.1 mmol) of acetic anhydride and 3.28 g (35.2 mmol) of 4-methylpyridine were added to the flask, stirred at room temperature for 30 minutes, and then heated to 70°C using an oil bath, and stirred for another 3 hours to obtain a reaction solution.
[0247] After the obtained reaction solution was cooled to room temperature, 647 g of methanol and 180 g of ion exchange water were added to obtain a precipitate of polyamide-imide. The precipitate was immersed in methanol for 12 hours, filtered and recovered, and washed with methanol. Next, the precipitate was dried under reduced pressure at 100° C. to obtain a polyamide-imide resin.
[0248] A composition for forming a base resin layer was prepared by adding N,N-dimethylacetamide (DMAc) to the obtained polyamideimide resin to a concentration of 15% by weight.
[0249] Preparation Example 2-3: Preparation of a composition for forming a base resin layer
[0250] A composition for forming a substrate resin layer was prepared in the same manner as in Preparation Example 2-1, except that 6.140 g (13.8 mmol) of 4,4'-(hexafluoroisopropyl)diphthalic dianhydride (6FDA) was used instead of 4.283 g (13.8 mmol) of 4,4'-oxydiphthalic dianhydride (OPDA), and 8.809 g (27.5 mmol) of 2-2'-bis(trifluoromethyl)benzidine (TFMB) and 3.889 g (18.3 mmol) of 2,2'-dimethylbenzidine (MB) were used instead of 14.67 g (45.8 mmol) of TFMB.
[0251] Preparation Example 2-4: Preparation of a composition for forming a base resin layer
[0252] In a 1L separable flask equipped with a stirring paddle, 52 g (162.38 mmol) of 2,2'-bis(trifluoromethyl)benzidine (TFMB) and 734.10 g of N,N-dimethylacetamide (DMAc) adjusted to a water content of 500 ppm were added under a nitrogen atmosphere, and TFMB was dissolved in DMAc under stirring at room temperature. Next, 28.90 g (65.05 mmol) of 4,4'-(hexafluoroisopropylidene)diphthalic dianhydride (6FDA) was added to the flask, and stirred at room temperature for 3 hours. Then, 28.80 g (97.57 mmol) of 4,4'-oxybis(benzoyl chloride) (OBBC) was added to the flask, and stirred at room temperature for 1 hour. Next, 7.49 g (94.65 mmol) of pyridine and 14.61 g (143.11 mmol) of acetic anhydride were added to the flask, and the mixture was stirred at room temperature for 30 minutes. The mixture was then heated to 70° C. using an oil bath and stirred for another 30 minutes to obtain a reaction liquid.
[0253] Then, the same procedure as in Preparation Example 2-1 was performed to prepare a base resin layer-forming composition.
[0254] Preparation Example 3: Preparation of hard coating composition
[0255] A hexafunctional urethane acrylate (UA-306I, Kyoeisha), 23 parts by weight of a dendritic acrylate (Miwon Specialty Chemical, Miramer SP1106), 50 parts by weight of methyl ethyl ketone, 3.5 parts by weight of 1-hydroxycyclohexyl phenyl ketone, and 0.5 parts by weight of a fluorine-containing UV-curable functional group compound (KY-1203, Shin-Etsu Silicone) were mixed using a stirrer and filtered using a PP filter to prepare a hard coating composition.
[0256] Examples and Comparative Examples: Production of Optical Laminated Body
[0257] Ultra-thin glass with thickness as shown in Table 2 below was prepared.
[0258] The primer layer forming composition of Preparation Example 1 was applied to one surface of the ultra-thin glass so that the thickness after drying was as shown in Table 2, and dried in an oven at 120°C for 2 minutes to form a primer layer. Then, the base resin layer forming composition shown in Table 2 below was applied on the primer layer using an applicator so that it had the thickness shown in Table 2 below after drying, and then heated in an oven at 80°C for 1 hour, and then dried in an oven at 210°C for 1 hour to form a base resin layer. Then, the hard coating composition of Preparation Example 3 was applied on the base resin layer so that the thickness after drying was as shown in Table 2, dried in an oven at 80°C for 2 minutes, and irradiated in a nitrogen atmosphere with a UV cumulative light amount of 600mJ / cm 2 Irradiation to form a functional coating.
[0259] [Table 2]
[0260]
[0261] Experimental example:
[0262] The physical properties of the optical laminates produced in the examples and comparative examples were measured by the following methods, and the results are shown in the following Table 3. In addition, when d1 is the thickness of the glass substrate and d2 is the total thickness of the primer layer, the substrate resin layer and the functional coating layer, the d2 / d1 value was calculated and shown in the following Table 3. In addition, the total thickness of the optical laminate was calculated and shown in the following Table 3.
[0263] (1) Elastic modulus of the base resin layer
[0264] Each of the compositions for forming a base resin layer of Preparation Examples 2-1 to 2-4 was applied to glass using an applicator so that the thickness after drying was 20 μm, and then dried in an oven at 80° C. for 1 hour and in an oven at 210° C. for 1 hour to form a base resin layer, which was then peeled off to obtain only the base resin layer.
[0265] The base resin layer thus obtained was used as a test piece for tensile evaluation using a supercut machine in accordance with the JIS-K7139 bar type standard, and the elastic modulus (GPa) of the test piece was measured at a tensile speed of 4 mm / min in a tensile evaluation mode of a universal testing machine.
[0266] (2) Pencil hardness
[0267] After fixing the optical laminate so that the hard coating layer faces the top, the pencil hardness was measured under a load of 750 gf. Using a pencil of the same hardness, the test was performed 5 times with a length of 1 cm, and the hardness that was OK (passed) 4 times or more was marked as the pencil hardness.
[0268] In addition, when the pencil hardness was measured, if the glass substrate of the optical laminate did not break under a load of 750 gf, it was marked as "OK", and if it was broken, it was marked as "NG (failure)".
[0269] (3) Bending resistance
[0270] Mandrel evaluation was performed at a curvature radius of 3 mm (so that the hard coat surface was folded inward) to observe the fracture of the optical laminate. Bending resistance was evaluated according to the following evaluation criteria.
[0271] <Evaluation Criteria>
[0272] OK: No breakage in the optical laminate
[0273] NG: The optical laminate is broken
[0274] (4) Curling characteristics
[0275] An optical laminate having a size of 10 cm×10 cm was produced and after being left at 25° C. and 48 RH % for 24 hours, the degree of lifting of each corner from the floor was measured. The curling property was evaluated according to the following evaluation criteria.
[0276] <Evaluation Criteria>
[0277] OK: The average height of the four corners is 3 mm or less.
[0278] NG: The average height of the four corners exceeds 3mm
[0279] [Table 3]
[0280]
[0281] As shown in Table 3, it can be confirmed that the optical laminates according to Examples 1 to 5 of the present invention (a primer layer, a substrate resin layer and a functional coating layer are formed on an ultra-thin glass having a thickness of less than 100 μm, such that the ratio of the total thickness (d2) of the primer layer, the substrate resin layer and the functional coating layer to the glass substrate thickness (d1) is controlled to be 0.1 to 0.4 and the elastic modulus of the substrate resin is controlled to be 3.3 to 5.2 GPa) not only have excellent pencil hardness characteristics, but also can ensure bending resistance and curling characteristics.
[0282] On the contrary, the optical laminate having a d2 / d1 value of less than 0.1 of Comparative Example 1 showed such low hardness characteristics that the lower glass substrate was cracked when the pencil hardness characteristics were measured, and the optical laminate having a d2 / d1 value of less than 0.4 of Comparative Example 3 showed that the pencil hardness, bending resistance and curling characteristics could not be simultaneously ensured. In addition, the optical laminate having a total thickness of the optical laminate of 120 μm or more of Comparative Example 2 showed that the bending resistance could not be ensured.
[0283] In addition, the optical laminates of Comparative Examples 4 and 5 having the elastic modulus of the base resin layer outside the range of 3.3 GPa to 5.2 GPa showed that pencil hardness, bending resistance, and curling characteristics could not be simultaneously ensured.
[0284] The above describes in detail the specific parts of the present invention. It should be clear to those skilled in the art that these specific technologies are only preferred embodiments and do not limit the scope of the present invention. Those skilled in the art will be able to make various applications and modifications within the scope of the present invention based on the above content.
[0285] Thus, the true scope of the invention should be defined by the appended claims and their equivalents.
[0286] [Explanation of Reference Numerals]
[0287] 110: Glass substrate 120: Primer layer
[0288] 130: Base resin layer 140: Functional coating layer.
Claims
1. An optical laminate, comprising: Glass substrate; A primer layer formed on one surface of the glass substrate; a substrate resin layer formed on the primer layer; as well as a functional coating layer formed on the substrate resin layer, The glass substrate is an ultra-thin glass with a thickness of less than 100 μm. The elastic modulus of the substrate resin layer is 3.3 GPa to 5.2 GPa, The pencil hardness of the optical laminate as a whole is 2H or more, and The optical stack satisfies the following mathematical formula 1: [Mathematical formula 1] 0.1≤d2 / d1≤0.4 In the mathematical formula 1, d1 is the thickness of the glass substrate, and d2 is the total thickness of the primer layer, the substrate resin layer, and the functional coating layer. 2 . The optical stack according to claim 1 , wherein the optical stack has a total thickness of less than 120 μm. 3 . The optical laminate according to claim 1 , wherein the primer layer is formed of a primer layer-forming composition containing at least one resin of a polyurethane resin and a polyester resin. 4 . The optical laminate according to claim 3 , wherein the primer layer is formed of a primer layer-forming composition comprising a water-dispersible polyurethane resin and a stabilizer, wherein the stabilizer comprises a primary heat stabilizer and an auxiliary heat stabilizer. 5 . The optical laminate according to claim 4 , wherein the primary thermal stabilizer is at least one selected from phenolic thermal stabilizers and amine thermal stabilizers, and the auxiliary thermal stabilizer is at least one selected from phosphorus thermal stabilizers and sulfur thermal stabilizers. 6 . The optical layered body according to claim 1 , wherein the base resin layer is formed of a base resin layer-forming composition containing at least one resin of a polyimide resin and a polyamide-imide resin. The optical stack according to claim 1 , wherein the functional coating layer is a hard coating layer. 8 . The optical laminate according to claim 7 , wherein the hard coating layer is formed of a hard coating composition comprising a light-transmitting resin, a fluorine-based UV-curable functional group-containing compound, a photoinitiator, and a solvent. 9 . An image display device comprising the optical layered body according to claim 1 . 10 . A window for a flexible display device, comprising the optical laminate according to claim 1 . 11 . A polarizing plate comprising the optical laminate according to claim 1 . 12 . A touch sensor comprising the optical laminate according to claim 1 . 13 . A variable transmittance optical stack comprising the optical stack according to claim 1 .
14. A smart window comprising the variable transmittance optical stack according to claim 13.
Citation Information
Patent Citations
Method for reinforcing glass for display by ion exchange of glass surface for generating compression stress on surface
KR1019990042313A